2010
DOI: 10.1016/j.jvlc.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Mental imagery and software visualization in high-performance software development teams

Abstract: This paper considers the relationship between mental imagery and software visualization in professional, high performance software development. It presents overviews of four empirical studies of professional software developers in high-performing teams: (1) expert programmers' mental imagery, (2) how experts externalize their mental imagery as part of teamwork, (3) experts' use of commercially available visualization software, and (4) what tools experts build themselves, how they use the tools they build for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Initially allowing the group-2 students to interact with objects and methods possibility formed the concrete understanding of the inner workings of OOP paradigm. Therefore, objects-first strategy, which is supplemented with visual interfaces, made the information apprehensible, apparent and visible to the learners [19,20]. We observed that the learners in group-2 could easily find, design or interpret the relevant information pertaining to programming tasks.…”
Section: Discussionmentioning
confidence: 91%
“…Initially allowing the group-2 students to interact with objects and methods possibility formed the concrete understanding of the inner workings of OOP paradigm. Therefore, objects-first strategy, which is supplemented with visual interfaces, made the information apprehensible, apparent and visible to the learners [19,20]. We observed that the learners in group-2 could easily find, design or interpret the relevant information pertaining to programming tasks.…”
Section: Discussionmentioning
confidence: 91%
“…However, it is argued that what is visualized is what can be visualized, not necessarily what needs to be visualized in peer academic literature [21]. Most studies try to develop new visualization techniques as oppose as to validate or add value to existing ones.…”
Section: Discussionmentioning
confidence: 99%
“…The software visualizations and visualization tools which experts build to support their own design activities tend to be designed for a specific context, rather than generic [Petre,28]. In one expert's characterisation of what distinguished his team's own tool from other packages they had tried: "the home-built tool is closer to the domain and contains domain knowledge".…”
Section: Insightmentioning
confidence: 99%